Beyond price and income: Preferences and food values in peri-urban Viet Nam. (1st November 2021) - Bell, Winnie; Coates, Jennifer; Fanzo, Jessica; Wilson, Norbert L.W.; Masters, William A.
Abstract: Sub-optimal diets are one of the most important risk factors contributing to the global burden of disease. Developing a better understanding of the drivers of food choice, including the role of individual preferences, is important to address this issue. The objective of this mixed methods research was to identify the relative importance of preferences for different food quality attributes (e.g. nutrition, food safety, price and convenience) that might influence shopping habits and food choice in the context of a rapidly changing peri-urban food environment in Hanoi Province, Viet Nam. A total of 264 women were randomly selected and interviewed using Best-Worst Scaling to elicit preferences among food quality attributes for different food groups (leafy green vegetables, fruits, instant foods, snack foods). A subset of these respondents (n = 40) participated in focus group discussions in order to explore their preferences and food values in more detail. The food quality attributes considered to be most important varied by food group with nutrition and food safety (both immediate and future health) ranking highest for leafy green vegetables and fruits, convenience for instant foods, and taste for snack foods. Price was considered least important across all food groups. Focus group discussions reinforced these results with additional insights particularly regarding trade-offs between nutrition, food safety, convenience, and price. This research demonstrates the feasibility of identifying important drivers of consumption in a South East Asian context using Best-Worst Scaling. These results could help inform the design of behavior change interventions and guide food system policies that seek to shift consumer choices towards healthier diets.